Intentional obesity reduction and the occurrence of gastric cancer – literature review - Gryta, Jakub; Bielak, Alicja; Iwan, Karolina; Janczewska, Martyna; Kania, Konrad; Kalicka, Maria; Krysa, Tomasz; Kolasa, Agata; Radziejowska, Zuzanna; Szklarz, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction: Gastric cancer (GC) is one of most common cancers worldwide. Reducing exposure to risk factors, along with screening and early detection, are crucial for prevention. Many studies have linked obesity to GC. Weight loss can be achieved through proper diet and exercise. For patients with a body mass index (BMI) of 40 or higher, or 35 or higher with serious obesity-related comorbidities, bariatric surgery can be a means of weight reduction. This raises the question of whether intentional weight loss can lower the risk of GC in the population. Purpose of the study: The aim of this study is to collect and summarize existing evidence on connection of bariatric surgery and lower GC risk and mortality in patients with obesity. Material and method: Literature review was performed, in English databases, using keywords : cancer, gastric cancer, bariatric surgery, prevention, obesity, survival in gastric cancer. Results and conclusion: It is widely recognized that obesity increases the risk of GC, and bariatric surgery is an effective method for weight reduction. Bariatric surgery is the most effective treatment for sustained weight loss and remission of obesity-related conditions. A systematic review conducted on this topic revealed that bariatric surgery is linked to a reduced risk of GC in patients with obesity. Compared to no surgery, bariatric surgery was found to be associated with significantly lower rates of obesity-associated cancer and cancer-related mortality. Weight loss after bariatric surgery provides significant health benefits.